Parish and Family in the Cultural Heritage of the Polish Emigrants to Texas in the Second Wave (1867) - Marek Liszka; Małgorzata Bujak (Perspektywy Kultury, 2023)
The article focuses primarily on the institutions of the parish and family in relation to the cultural heritage of Polish Texans of the second wave since 1867. Reaching back to the beginnings of Polish emigration to the United States, which is associated with the settlement of Panna Maria in Texas by emigrants from Opole Silesia, the article presents the second wave of emigration from Galicia and Greater Poland. The analysis was based on the archival materials of the Polish Genealogical Society of Texas (PGST), which cover the periods from 1984 to 2021. The research material was collected from 124 PGST volumes (4,358 pages). The document proves that both the parish and the family were the basic units in the lives of Polish emigrants, around whom everyday family, social and religious life revolved.